Anti-Apoptotic Proteins Mcl-1 And Bcl-Xl Are Crucial For Nasopharyngeal Carcinoma Cell Survival - Abdul Rahman, Siti Fairus (2022)
Malaysia has one of the highest national incidences of Nasopharyngeal carcinoma (NPC) in South-East Asia. Treating patients with metastatic NPC is often a challenge as patients develop resistance to systemic anti-cancer therapies such as chemotherapy and retreating local recurrence with radiotherapy have many limitations. Hence, improved treatment strategies are needed for better patient outcome. Upregulation of the anti-apoptotic protein BCL-2 is one of the strategies that cancer cells adopt to evade cell death. Hence, these proteins have become attractive therapeutic targets. Given that different cell population rely on different anti-apoptotic proteins for survival, it is crucial to determine which proteins are important for NPC cell survival. Previous study reported that co-inhibition of BCL-2 and BCL-XL did not induce cell killing in NPC cells, which indicate that either MCL-1 or BFL-1 may play an important role in the survival the NPC cells. Given that the roles of MCL-1 and BFL-1 for NPC cell survival are under-explored, this study will primarily focus on delineating the functional roles of these two molecules for cell survival using gene editing and pharmacological approaches.